Development of a Preparative Method for Obtaining an Enantiomerically Pure Substance of Salbutamol by Supercritical Fluid Chromatography - V. N. Tsarev; N. G. Bazarnova; I. V. Mikushina (Разработка и регистрация лекарственных средств, 2022)
Introduction. An increasing number of studies conducted in various countries in the field of biopharmacy convincingly show the differences in the physiological effects on the human body of stereoisomers of pharmaceutical substances. As a rule, one of the enantiomers has the necessary pharmacological effect, the other enantiomer is either inert or has a negative side effect. Currently, it is important to obtain enantiomerically pure pharmacological substances from their racemic mixtures.Aim. Obtaining the R-isomer of salbutamol from a racemic mixture of salbutamol and developing a preparative procedure for chiral separation by supercritical fluid chromatography (SFC) with a yield of the target product sufficient for the production process.Materials and Methods. Supercritical fluid chromatography (SFC) is widely used for analytical and preparative separations of enantiomers of pharmaceutical substances. The relevance of the use of supercritical fluid chromatography SFC is largely due to the fact that it uses sub- or supercritical carbon dioxide (SC-CO2) as the main component of the mobile phase (MP). Studies were carried out on semi-preparative Investigator SFC (Waters Corporation, USA) and preparative Prep 200 qSFC (Waters Corporation, USA) supercritical fluid chromatographs with PDA detectors. Samples were weighed to the nearest 0.0001 g on a XPE206DR balance (Mettler Toledo, USA).Results and discussion. The process of chiral separation of salbutamol sulfate by the SFC method on Prep 200 qSFC (Waters Corporation, USA) was studied. It was revealed that in the chromatographic system under supercritical conditions, the salt is separated into acidic and basic residues, which significantly reduces productivity and shortens the duration of continuous operation of the chromatograph. Conditions for the preparative chiral separation of the racemic mixture of salbutamol base into R- and S-isomers with high enantioselectivity and productivity have been developed. The resulting R-isomer of salbutamol base can be converted into the pharmaceutical substance in the form of sulfate or other salt without loss of enantiomeric purity, the S-isomer can be subjected to racemization and subsequent use.Conclusion. A preparative method has been developed for the chiral separation of a racemic mixture of salbutamol by supercritical fluid chromatography (SFC) with a yield of the target product (R-isomer) of 5.5 g per shift (8 hours).